A time of technological change [ICTs for agriculture] - Painting, Kevin A. (Technical Centre for Agricultural and Rural Cooperation, 2009)
ICTs have gone through incredible changes in the last decade, but innovation is not only driven by manufacturers, it often comes from individuals adapting technology to suit local needs.